A study of the relationship between market price of property and residential environment in the suburb of Wynberg, Cape Province - Goold-Verschoyle, Anna Mary (School of Architecture, Planning and Geomatics, 2021)
This Thesis investigates the residential structure of Wynberg, a suburb of Cape Town, and it has both a short and long term purpose. The main intent of the Thesis is contained in its short term purpose, that is it attempts to find patterns of selective differentiation in residential location for various groups in the community. An assessment of the factors that are most salient in the location of households must begin with an appreciation of the range of the relevant variables which will vary according to the scale of the project and the general mode of analysis that is contemplated. It is not intended in this study to examine the interaction between those variables such as population, economic organisation, technology and environment which would be expected to play a role in shaping a macroscale study of residential structure at Metropolitan level. The general mode of analysis here is on the suburban or microscale and it is intended to compare various attributes associated with environmental quality (using an experimental vocabulary and scoring system) with a constant unit of measurement studied over time. This unit of measurement is the market price of property adjusted for comparability over time and for which a large source of primary data is available in the records of property transactions in the Valuation Department of the Cape Town City Council. It is assumed that the price people pay for dwellings is a good index of.socio~ economic status and that decisions made in the market place are by and large rational ones. Wynberg was chosen because it ·appeared to have a wide range of residential building types in various income groups and because it contained both White and Coloured Group Areas with little induced change due to Government legislation. The study is restricted in deptp to transactions in the property market between the years 1963 to 1967. It was originally intended to study a ten year period, but the length of time taken to procure the data from the Valuation Department precluded so long a study. The evaluation of environmental quality includes physical, perceptual and social factors and a necessary part of the study is a testing of the expeF.imental vocabulary and scoring system. The variables to be studied in the analysis are therefore qualit~tive in the case of environment and quantitative in the case of the market price of property. The long term purpose of the study is to find a benchmark for further study on a city-wide scale of the locational patterns of high value residential areas. Before such a study could be undertaken some assumption would have to be made about 'high value residential areas'. What are the factors which influence location in Aigh value residential areas? One could postulate that a high scoring on the environmental quality scale would be a more significant factor in location in higher value areas than accessibility to work place, or to public transport routes. Therefore, if a positive correlation was found between environmental quality and high market price in the Wynberg area, a threshold market value might be revealed above which one couid study high value locational patterns throughout the Metropolitan area. Analysis of high value areas was carried out by the Chicago School of Ecologists in the 1920's when American cities were experiencing the first rapid expansion to the suburbs, brought about by wide spread use of the automobile in a period of increasing economic growth and affluence. Since then, according to Leo F. Sc0 hnore (i), studies of ecological structure have been carried out in at least one city in every major region of the world. To the writer's knowledge, no such study has yet been carried out into the locational patterns of high class residential areas in South African cities. The Thesis is divided into three parts. The first summarises research in the related fields of residential structure, environmental psychology and urban design. The second part is the main body of the Thesis containing the Wynberg Case Study and the third part is concerned with conclusions.